A brief description of an intellectual journey - le Roux, J. (1994)
This article is devoted to a brief descriptionption of Willem Vorster's intellectual journey. As a New Testament scholar Vorster exerted a great influence on the study of the New Testament in South Africa. Since the beginning of the nineteen seventies New Testament studies took a different direction and Vorster's contributions in this regard were decisive. To illustrate this development in South African New Testament scholarship this article focuses on Vorster's preoccupation with method and related issues. He introduced a new kind of approach to the New Testament which was constantly changed or remodified. Vorster changed or at least shaped the thoughts of a generation of New Testament scholars regarding method, the nature of the text, the reference to outside realities, the intentions of the original authors, et cetera. His approach also reflects his lifelong struggle to come to grips with history and historical criticism.
Keywords: W.S; Vorster; Linguistics; Historical criticism; Theology; Christianity